Perancangan Sistem Informasi Pendaftaran Siswa Baru SMA IT Iqra Bengkulu - nadiza lediwara (Universitas PGRI Yogyakarta, 2022)
The new student registration system at SMA IT Iqra Kota Bengkulu has been carried out since its establishment until now which is done manually. Weaknesses that arise are the number of registrants that are more than 30 students per day and the limited number of employees. This research provides convenience from various forms of weaknesses, including time efficiency, ease of administrative governance, and the absence of a manual queuing system. Other advantages include reducing paper usage on registration forms and schedules. Therefore, the new student registration system is able to provide solutions for employees, prospective students, and schools.